A Propensity Score Matched Analysis Comparing Outpatient and Short-Stay Hospitalization to Standard Inpatient Hospitalization Following Total Ankle Arthroplasty - Mark A. Plantz BS; Alain E. Sherman BA; Anish R. Kadakia MD (Foot & Ankle Orthopaedics, 2020)
Category: Ankle Introduction/Purpose: The number of total ankle arthroplasties (TAAs) performed annually has continued to increase over the last two decades. Given the current challenges of healthcare cost-control, the trend towards minimizing hospitalization and length of stay (LOS) after various procedures, including joint replacement, has become an area of interest. Currently, there are no large sample, propensity score matched analyses to assess the safety of ‘short-stay’ versus standard inpatient hospitalization following TAA. Methods: The American College of Surgeons’ National Surgical Quality Improvement Program (ACS NSQIP) was used to identify 1,141 patients who underwent primary and revision TAA between 2007 and 2017. Propensity score matching was used to compare the risk of 30-day unplanned readmission, reoperation, mortality, discharge destination, and several medical and surgical complications in patients with outpatient or short-stay inpatient hospitalization (LOS <= 1 day) versus standard inpatient hospitalization (LOS > 1 day). Patients were matched in a 1:1 ratio based on several factors, including age, sex, body mass index (BMI), American Society of Anesthesiologists (ASA) classification, and several comorbidities (diabetes, smoking, COPD, congestive heart failure, hypertension, dialysis, and chronic steroid use). The incidence of various 30-day complications were compared between the two propensity score matched groups to assess for any differences in short-term outcomes after controlling for confounding risk factors. Results: A total of 892 patients were included in the propensity-score matched analysis, with 446 patients per group. The shorter LOS group had a significantly lower rate of medical complications (0.2% vs. 2.8%, p = 0.004) and non-home discharge (1.3% vs. 12.1%, <0.001). Additionally, the shorter LOS group had lower rates of unplanned readmission (0.4% vs. 1.1%, p = 0.256), reoperation (0.2% vs. 0.4%, p = 0.564), return to the OR (0.2% vs. 0.9%, p = 0.179), and surgical complications (0.4% vs. 2.0%, p = 0.057), although these results were not statistically significant. Conclusion: Propensity score matched comparative analysis demonstrated that outpatient and short-stay inpatient hospitalization can be just as safe as standard inpatient hospitalization after TAA. Length of stay should be dictated by the overall risk of complication. Outpatient or short-stay TAA should be considered for patients with low risk of short-term complications.